Implementation of Nurses’ Rights in Medical Services at The Dr. Dradjat Prawiranegara Regional General Hospital Based on Law No. 38 of 2014 on Nursing - Dhea Maulidya; Ikomatussuniah Ikomatussuniah; Ahmad Lanang Citrawan (Anthroposia: Journal of Social and Human Development, 2026)
Dr. Dradjat Prawiranegara Regional General Hospital, as a public healthcare institution, is obligated to deliver high-quality and professional medical services. Law Number 38 of 2014 on Nursing provides nurses with legal rights and protection in performing their duties. However, in practice, these rights have not been optimally implemented, necessitating an evaluation of their enforcement. This study addresses how nurses’ rights are implemented in medical services at Dr. Dradjat Prawiranegara Hospital based on Law Number 38 of 2014, as well as the obstacles and efforts associated with their realization. The research applies the theories of Legal Protection and Legal Certainty. It employs an empirical juridical method with a descriptive qualitative analytical approach. Data sources include primary and secondary data, consisting of primary, secondary, and tertiary legal materials, collected through literature review and field research. The findings indicate that the implementation of nurses’ rights includes legal protection, safe working conditions, and opportunities for professional development. Nonetheless, challenges persist, such as limited resources, high workloads, and insufficient awareness among stakeholders regarding the importance of fulfilling nurses’ rights. Efforts to address these issues involve strengthening internal hospital policies, continuous professional guidance, and consistent legal assistance for nurses.